PENDAMPINGAN DIGITAL MARKETING KRUPUK PATAK KHAS PASURUAN DI KAMPUNG BAHARI DESA SEMARE BERBASIS KEARIFAN LOKAL TRADISI PETIK LAUT DAN PRAONAN - Ahmad Marzuki; Dzaki Muhammad Afi Fuddin; Munif (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service program aims to assist MSMEs in strengthening their brand identity, implementing digital marketing strategies based on local wisdom, and fulfilling business legality requirements. The methods used include field observation, interviews, branding training, digital marketing workshops, and assistance in registering a Business Identification Number (NIB) and halal certification. The results of the activity indicate an increase in business awareness of the importance of legality, brand identity, and the use of digital media. Krupuk patak is developed through logo design, attractive packaging, and storytelling-based promotions that highlight local cultural values ​​such as the Petik Laut and Praonan traditions. Assistance with business legality has a positive impact on credibility and expanding market access. This activity is the first step in strengthening the coastal community economy based on local potential and culture.